Diseño de un parque lineal recreativo en el río “Calabí”, recinto los cerritos, cantón Quinsaloma provincia de Los Ríos - Padilla Velasco, Lady Diana (2014)
This thesis was aimed to design a linear recreational park in the " Calabí" river precinct Los Cerritos Region Quinsaloma Los Rios province , aimed potentiate the attraction, culture, gastronomy, natural resources and infrastructure sector. The main objectives that were raised in this study were diagnosed green area along the banks of the river Calabí, conduct a market study to analyze the expectations and recreational benefits of the population, and plan the area for public use. To carry out the research methods were used; inductive, deductive and analytical, while the types of research were; applied, descriptive and documentary techniques were constituted by the survey and observation. The green area on the banks of river Calabí represents a tourist attraction, as it has flora and fauna. The green area of the complex presented by Los Cerritos attraction inventory shows the physical, natural features and the basic infrastructure of the place. As for the market study it was determined that 100% of those surveyed in the canton Quinsaloma, they would like on-site Los Cerritos, a recreational linear park is built, the same that serves as security, entertainment, cleanliness, accessibility, food service, parking, restrooms, tourist facilities, tourist guide, etc. The recreational linear park will be established in an area of 35,763.88 m2, distributed equally by areas such as; sports, dayroom, playground, picnic and rest, food court, shopping, water area, trails, parking, medical clinic, gazebo, camping, bathrooms and closets.